Early childhood education in Jamaica: A project monograph (Bernard Van Leer Foundation, 1972)
After an overview of the development of early childhood education in Jamaica, this monograph provides a report on the work of the Project for Early Childhood Education (PECE)
Keywords: Early childhood care and education